Age‐adjusted D‐dimer to rule out deep vein thrombosis: findings from the PALLADIO algorithm. (8th December 2017) - Riva, N.; Camporese, G.; Iotti, M.; Bucherini, E.; Righini, M.; Kamphuisen, P. W.; Verhamme, P.; Douketis, J. D.; Tonello, C.; Prandoni, P.; Ageno, W.; ,
Abstract : Essentials The accuracy of the age‐adjusted D‐dimer in suspected venous thromboembolism is still debated. We assessed the performance of age‐adjusted D‐dimer combined with the PALLADIO algorithm. The age‐adjusted threshold can reduce the need for imaging tests compared to the fixed cut‐off. The safety of this approach should be confirmed in large management studies. Summary: Background: Age‐adjusted D‐dimer has been proposed to increase specificity for the diagnosis of venous thromboembolism (VTE). However, the accuracy of this threshold has been recently questioned. Objectives: To assess the diagnostic performance of age‐adjusted D‐dimer combined with clinical pretest probability (PTP) in patients with suspected deep vein thrombosis (DVT). Methods: PALLADIO (NCT01412242) was a multicenter management study that validated a new diagnostic algorithm, incorporating PTP, D‐dimer (using the manufacturer's cut‐off) and limited or extended compression ultrasonography (CUS) in outpatients with clinically suspected DVT. Patients with unlikely PTP and negative D‐dimer had DVT ruled out without further testing (group 1); patients with likely PTP or positive D‐dimer underwent limited CUS (group 2); patients with likely PTP and positive D‐dimer underwent extended CUS (group 3). Patients with DVT ruled out at baseline had a 3‐month follow‐up. In this post‐hoc analysis we evaluated age‐adjusted D‐dimer cut‐off (defined as age times 10 μg L −1, or age times 5 μg L −1 for D‐dimers with a lower manufacturer's cut‐off, in patients > 50 years). Results: In total, 1162 patients were enrolled. At initial visit, DVT was detected in 4.0% of patients in group 2 and 53.0% in group 3. The age‐adjusted D‐dimer, compared with the fixed cut‐off, resulted in 5.1% (95% CI, 4.0–6.5%) reduction of CUS. The incidence of symptomatic VTE during follow‐up was: 0.24% (95% CI, 0.04–1.37) in group 1; 1.12% (95% CI, 0.44–2.85) in group 2; and 1.89% (95% CI, 0.64–5.40) in group 3. Conclusions: The PALLADIO algorithm using age‐adjusted D‐dimer slightly decreased the number of required imaging tests, but this approach should be confirmed in large management studies.